SUFISTIC VALUES IN POLITICAL LEADERSHIP: A SOCIAL-POLITICAL ANALYSIS OF SYECH MUSTOFA HUSEIN NASUTION IN NORTH SUMATRA - Saipul Bahri; Mohd Syakir Bin Mohd Rosdi (Academic Solution Publisher, 2025)
This article examines the role of Sufistic values in shaping models of political leadership through a socio-political analysis of Syech Mustofa Husein Nasution, a prominent Mandailing ulama whose influence extends from spiritual domains to political and social arenas in North Sumatra. While studies on Islamic leadership in Indonesia have predominantly focused on institutional politics, party dynamics, and electoral behavior, relatively few have explored how Sufistic ethics operate as a source of political legitimacy and developmental paradigms. Addressing this gap, the study elucidates how Syech Mustofa Husein Nasution synthesized spirituality, ethics, education, and communal engagement to produce a model of political leadership rooted in tawhid, amanah, shura, and wasatiyyah. Methodologically, this work adopts a qualitative descriptive approach, relying on primary documents, historical accounts, interviews, and pesantren-based observations. The findings demonstrate that Sufistic values not only functioned as moral resources but also as socio-political capital enabling community mobilization, conflict mediation, cadre formation, and institutional activism. These insights reveal that Sufism in the Indonesian context is neither apolitical nor purely devotional, but can serve as an ethical-political framework for social development. The study contributes to broader discussions on Islamic political thought by highlighting how spiritual authority intersects with governance and public leadership, offering implications for contemporary Islamic leadership, community-based development, and the revitalization of ethical politics in Muslim societies.